Prevention and Early Detection Anemia in Adolescents with Hemoglobin Examination and Administration of Iron Supplements - Pratiwi Puji Lestari (Borneo Community Development, 2022)
Introduction: anemia in adolescents will have an impact on the sustainability of reproductive health throughout the life cycle of women, especially during childbirth and pregnancy. which is not adequate. The purpose of this community service activity is to carry out early detection efforts by checking hemoglobin and giving iron supplements to adolescent girls. Methods: the activity is carried out by checking hemoglobin and giving blood-added tablets. The targets for this community service activity are teenagers at elementary school age (ages 9-12 years) who are already menstruating. the tools and materials used were handscoons, digital haemometers, disinfectant swabs, lancets, needles and iron supplements given to teenagers. Results: the results of hemoglobin measurements showed that all adolescents did not have anemia because the overall hemoglobin measurement results were above 12 g/dL. Conclusion: Early detection efforts with hemoglobin examination and iron supplementation were carried out with the overall result that young women at SDN Karang Indah did not experience anemia after the examination.